Violence and Sex and Violence Again: The Sexual Revolution in the Films of the Yugoslav Black Wave - Patrycjusz Pająk (Slavia Meridionalis, 2022)
Violence and Sex and Violence again: The Sexual Revolution in the Films of the Yugoslav Black Wave